Ferrous Materials Steel and Cast Iron - Berns, Hans; Theisen, Werner (Springer Berlin Heidelberg : Imprint: Springer, 2008)
Ferrous materials have made a major contribution to the development of modern technology. They span a tremendous range of properties and applications. Part A of this book is dedicated to the fundamental relationships between the structure and the properties of ferrous materials. The considerably larger Part B deals with standardised materials, recent developments and industrial applications, which also affect processing aspects. Details are given for general engineering materials, tool and functional materials, as well as high-strength, stainless, creep-resistant and wear-resistant grades. This book closes the gap in the treatment of steel and cast iron. Each chapter takes into account the gradual transitions between the two types of ferrous materials. The authors demonstrate that steel and cast iron are versatile and customisable materials which will continue to play a key role in the future. Hans Berns Born 1935, studied ferrous metallurgy, worked in the specialized steel industry from 1959 to 1979, doctorate TH Aachen 1964, habilitation TU Berlin 1975, held the Chair of Materials Technology at the Ruhr-University Bochum from 1979 to 2000. Werner Theisen Born 1957, studied mechanical engineering, research assistant and chief engineer at the Ruhr-University Bochum up to 1995, doctorate 1988, habilitation 1996, worked in the mechanical-engineering industry until 2000, has held the Chair of Materials Technology of the Ruhr-University Bochum since 2000.